Daylight, design and place-making - Elkadi, Hisham; Al-Maiyah, Sura (Abingdon, Oxon ; New York : Routledge, 2021)
"Daylight, Design and Place-Making examines the role of daylight in creating and revealing the wonders of heritage and contemporary architecture. Shifting from a purely technical approach to daylighting, this book places importance on the creation of meaningful aesthetics through an understanding of context and culture. Cultural applications of light in architecture differ depending on various historical, technological, and social characteristics. Increasingly, there is a revival of interest in contemporary architecture using daylight as an essential contextual ingredient in the design process. By examining the architecture of daylight in different locales and setting these in their historical contexts, the book argues that appropriate use of daylight will ensure not only visual and thermal comfort in the urban setting and aid in energy efficiency, but also will contribute to the overall identity of new buildings, particularly in urban regeneration projects. This book brings together an analysis of technical aspects of daylight performance and environmental impact, with discussions on the psychology of daylighting and its influence in shaping perceptions of our built environment. It will be an ideal read for academics and researchers interested in architecture and cultural studies"--
History of light, shades and shadows -- Structures of light : daylight and place making -- Reading daylight -- Daylight and health -- Delight of heritage.
OCLC-licensed vendor bibliographic record.
Keywords: Daylighting; Architecture -- Human factors; Place (Philosophy); ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning